Integration of Artificial Intelligence in E-learning: Distance Education Students' Responses - Marisa; Dewi Artati Padmo Putri; Mujiono; Ami Hibatul Jameel (Universitas Pendidikan Ganesha, 2024)
One of the common issues frequently complained about by students pursuing distance education is the delay in responses from professors or tutors in online discussion forums and the assessment of assignments on the e-learning platform. Students require timely feedback as an essential part of their learning process. Feedback given promptly plays a crucial role in enhancing students' motivation for self-directed learning. This research aims to explore students' responses to the integration of Artificial Intelligence (AI) in the Moodle e-learning platform at Universitas Terbuka. A survey was conducted involving 435 students from 40 branch offices of Universitas Terbuka located in Indonesia and abroad. Data were collected through a survey method that began with the design of a questionnaire using Google Forms, which was then distributed through student WhatsApp groups. The survey instrument was designed to gauge students' responses to the AI features provided, including feedback for essay assignments, plagiarism checking support, learning materials with automatic assessment, course recommendations based on student profiles, and predictive grades based on student scores and participation. Respondents were asked to provide their answers on a Likert scale (1-10) and open-ended questions. The research results indicate that the majority of respondents gave positive feedback on all presented features. This positive response suggests that the integration of AI into the e-learning platform has the potential to enhance the learning experience and academic performance of students.